Alterations in coagulation, fibrinolysis and complement during cardiopulmonary bypass with heparin-coated oxygenator - HORIKOSHI S.; NAKANO M.; HASHIMOTO K.; EMOTO H.; KOYANAGI K.; KANAZAWA T.; KUROSAWA H. (Jinko Zoki, 1993)
Changes of coagulation, fibrinolysis and complement activation during and post cardiopulmonary bypass were studied using heparin-coated membrane oxygenator (Carmeda Maxima®: 5 cases) and compared with non-coated membrane oxygenator (Maxima®: 5 cases). Both oxygenator showed good gas exchange capability. Platelet loss was more and leucocytes less increased in the coated group with no intergroup differences. Activation of coagulation and fibrinolysis was observed during cardiopulmonary bypass, however no significant differences were seen between two groups. In the heparin-coated group consumption of complements and production of anaphylatoxins were singnificantly reduced. These results suggest the heparin-coated oxygenator improves biocompatibility by reducing complement activation. ヘパリン結合人工肺(Carmeda Maxima®)を開心術5例(C群)に使用し、ガス交換能、血球・凝固・線溶・補体系の変動を経時的に測定し、ヘパリン非結合人工肺の5例(NC群)と比較し、その影響について検討した。その結果、1) PaO2、PaCO2は体外循環中、各々300mmHg以上、30mmHg以下を保ち両群とも充分なガス交換能を示した。2) 血小板はC群の減少が大きかったが有意差はなかった。3) 白血球数はNC群の方がより増加する傾向を認めた。4) 体外循環中にもかかわらず、凝固・線溶系の活性化が認められた。C群の方がより強く活性化される傾向だったが、両群問に有意差は認めなかった。5) 補体系ではC群で補体(C3, C5)の消費が少なく、anaphylatoxin (C3a, C5a)の産生も少ないことが、一部(C3, C5a)で有意差(P<0.05)をもって認められた。以上より、ヘパリン結合人工肺は、従来型の人工肺に比し補体の活性化が少なく、より生体適合性の高い人工肺であると考えられた。